SRIKANDI Digital Archiving Implementation: Effectiveness and Impact on Secondary Education Units in Riau Islands Province - Supanto Nababan; Rumzi Samin; Okparizan Okparizan (Manunggal Halim Jaya, 2026)
This study is to evaluate the execution of Sistem Informasi Kearsipan Dinamis Terintegrasi (SRIKANDI) at secondary educational institutions within Riau Islands Province to facilitate the digitalization of regional archive management. The research backdrop is founded on the necessity for archival modernization in island regions confronting geographical obstacles, restricted internet access, and disparities in human resource competencies. The study employs a descriptive qualitative methodology, utilizing data gathering approaches such as observation, interviews, and documentation. The data analysis employs the interactive model of Miles & Huberman, whilst the efficacy of policy execution is assessed by four theoretical indicators proposed by Edwards III: communication, resources, disposition, and bureaucratic structure. The research findings indicate that the adoption of SRIKANDI at the secondary school level is beneficial. Communication among the education department, schools, and technical implementers is maintained by regular socialization and training. Human resources and supporting infrastructure are deemed sufficient for the digitization of archives; nonetheless, many schools in remote areas continue to encounter limitations in internet connectivity and technical adaptation. The executor's disposition demonstrates a strong commitment and favorable acceptance of the digital system. An explicit bureaucratic framework, encompassing systematic reporting and oversight systems, facilitates the effective execution of policies. In summary, SRIKANDI has demonstrated enhancements in administrative efficiency, file management organization, and public transparency and accountability. The study advocates for enhanced technical support, the optimization of the application throughout the archiving process, and additional investigation into the influence of SRIKANDI on various managerial dimensions within the educational context.